Analysis of heavy metal accumulation in fish at Terengganu Coastal Area, Malaysia - M.N.R. Rosli,; S.B. Samat,; M.S. Yasir,; M.F.M. Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Bioaccumulation of toxic metals in fish causes serious threats to human when they are consumed. Thus, the detection of toxic element concentration levels in aquatic component is important. The accumulation of some heavy metals such as Cd, Cu, Fe, Mn, Pb and Zn in fish were determined. Ten species (Selaroides leptolepis, Decapterus maraudsi, Epinephelus lanceolatus, Priacanthus tayenus, Rastrelliger, Megalaspis cordyla, Nibea soldado, Pristipomoides filamentosus, Bramidae and Siganus canaliculatus) were collected from Terengganu coastal area, Malaysia. The analysis was done using inductive coupled plasma-mass spectrometer (ICP-MS) technique. In general, the concentration levels of heavy metals in fish samples are lower than the previous study in various locations. The highest average level of heavy metal recorded in fish is Fe followed by Zn, Mn, Cu, Cd and Pb. The metal concentration found in this study was lower than the national and international recommended dietary allowance (RDA) for human consumption except Fe (52.33 × 10-2 ± 6.39 × 10-2 mg kg-1) which exceeded the limit of 0.3 mg kg-1. Long term monitoring system of metal bioaccumulation in fishes need to be done to provide useful information for the assessment of the potential health risks of metals in Malaysia.